Evaluation of Nano-Zn, Inorganic, and Organic Nutrient Management Strategies and Their Effects on Growth Indices in Kharif Maize (Zea mays L.) - , Shikhar Verma; , D. D. Yadav; , V. K. Verma; , M. Z. Siddiqui; , Ravindra Kumar; , Sarvesh Kumar; , Shravan Kumar Maurya; , Mandeep Kumar; , Sunil Kumar Prajapati (Archives of Current Research International, 2024)
The investigation was carried out during the Kharif seasons of 2022 and 2023 at the Students' Instructional Farm, Department of Agronomy, Chandra Shekhar Azad University of Agriculture & Technology, Kanpur. To assess the impact of various nutrient management strategies, including Nano-Zn, inorganic, and organic methods, on the growth and yield of Kharif maize. A Split-Plot Experimental design was employed, incorporating three replications. Organic manures-specifically a control, farmyard manure (FYM) applied at 10 t/ha, and vermicompost applied at 5 t/ha-were assigned to the main plots. Meanwhile, nutrient management treatments (including a control, 75% RDF, 75% RDF + ZnSO4, 75% RDF + Nano-Zn, 100% RDF, 100% RDF + ZnSO4, and 100% RDF + Nano-Zn) were allocated to the sub-plots. The maize variety chosen for the study was DKC-9144. The soil at the experimental site was characterized by a sandy loam texture, with a pH ranging from 7.72 to 7.67, a bulk density of 1.37 Mg/m³, and organic carbon levels between 0.43% and 0.44%. The location of the site is within the Indo-Gangetic Plain, which is typified by a subtropical climate and an average annual rainfall of about 890 mm. Throughout the experiment, data were collected on key growth parameters such as the crop growth rate (CGR), relative growth rate (RGR), and absolute growth rate (AGR) at different stages of maize development (30-60 days after sowing, 60-90 days after sowing, and from 90 days after sowing until harvest). Results indicated that the treatment involving 100% RDF combined with Nano-Zn at 10 ml/litre produced the highest growth rates, while 100% RDF + ZnSO4 also showed significant results. Among the organic treatments, vermicompost at 5 t/ha proved to be more effective than FYM, highlighting the superior role of Nano-Zn and advanced nutrient management practices in promoting the growth and yield of Kharif maize.